Three-Dimensional Reconstruction of Murine Peyer's Patches from Immunostained Cryosections. (4th November 2013) - Ahlawat, Sarita; De Jesus, Magdia; Khare, Kedar; Cole, Richard A.; Mantis, Nicholas J.
Abstract: Peyer's patches, macroscopic aggregates of lymphoid follicles present throughout the small intestines of humans and other mammals, are considered the gateway through which luminal dietary antigens and microbes are sampled by the mucosal immune system. The cellular make-up of Peyer's patch lymphoid follicles is not only complex, but highly dynamic, as there are at least four major cell types that are known to migrate in response to antigenic stimulation. In an effort to capture the complexity and dynamic nature of this specialized tissue, here we report the three-dimensional (3D) reconstruction of immunofluorescent-labeled mouse Peyer's patch cryosections. The technology that enabled the stacking and linear blending of serial cryosections was a novel macro for Fiji, the open source image-processing package based on ImageJ. By simultaneously labeling cryosections for surface markers CD45R, CD3, and CD11c, we provide a 3D image as well as quantitative measures of B-cell, T-cell, and dendritic cell populations at steady state and following exposure to the mucosal adjuvant cholera toxin.